Impact of holding the baby following stillbirth on maternal mental health and well-being: findings from a national survey - Redshaw, M; Hennegan, J; Henderson, J (BMJ Publishing Group, 2016)
Objectives To compare mental health and well-being outcomes at 3 and 9 months after the stillbirth among women who held or did not hold their baby, adjusting for demographic and clinical differences. Design Secondary analyses of data from a postal population survey. Population Women with a registered stillbirth in England in 2012. Methods 468 eligible responses were compared. Differences in demographic, clinical and care characteristics between those who held or did not hold their infant were described and adjusted for in subsequent analysis. Mental health and well-being outcomes were compared, and subgroup comparisons tested hypothesised moderating factors. Outcome Measures Self-reported depression, anxiety, post-traumatic stress disorder (PTSD) symptoms and relationship difficulties. Results There was a 30.2% response rate to the survey. Most women saw (97%, n=434) and held (84%, n=394) their baby after stillbirth. There were some demographic differences with migrant women, women who had a multiple birth and those whose pregnancy resulted from fertility treatment being less likely to hold their baby. Women who held their stillborn baby consistently reported higher rates of mental health and relationship difficulties. After adjustment, women who held their baby had 2.12 times higher odds (95% CI 1.11 to 4.04) of reporting anxiety at 9 months and 5.33 times higher odds (95% CI 1.26 to 22.53) of reporting relationship difficulties with family. Some evidence for proposed moderators was observed with poorer mental health reported by women who had held a stillborn baby of <33 weeks’ gestation, and those pregnant at outcome assessment. Conclusions This study supports concern about the negative impact of holding the infant after stillbirth. Results are limited by the observational nature of the study, survey response rate and inability to adjust for women's baseline anxiety. Findings add important evidence to a mixed body of literature.